1983
DOI: 10.1177/136346158302000301
|View full text |Cite
|
Sign up to set email alerts
|

American Indian Psychiatric and Social Problems

Abstract: This paper is an overview of the past 15 years of research on American Indian psychiatric and social problems. Since the development of the first mental health program in the Indian Health Service (IHS) in 1967, there has been a significant increase in published articles on this topic. The number of relevant citations has doubled each decade, rising from 48 in the 1930s to 759 in the 1970s (Kelso and Attneave 1981). More important, in the past decade we have witnessed greater participation by American Indian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Increasing youth suicide rates have been documented with rates increasing for males aged 15–25 years, from 4.1 to 12.1 per 100 000 between 1958 and 1982 35 . However, intergroup differences are considerable 18 with rates up to the 1970s varying from 8 to 120 per 100 000 36,37 . Similar caveats are suggested in a recent review, which pointed to a three‐fold increase among adolescents and young adults to levels some two to three times higher than for the nation as a whole, with males constituting approximately two‐thirds of all suicides between 15 and 34 between 1979 and 1992 11 .…”
Section: Epidemiologymentioning
confidence: 64%
“…Increasing youth suicide rates have been documented with rates increasing for males aged 15–25 years, from 4.1 to 12.1 per 100 000 between 1958 and 1982 35 . However, intergroup differences are considerable 18 with rates up to the 1970s varying from 8 to 120 per 100 000 36,37 . Similar caveats are suggested in a recent review, which pointed to a three‐fold increase among adolescents and young adults to levels some two to three times higher than for the nation as a whole, with males constituting approximately two‐thirds of all suicides between 15 and 34 between 1979 and 1992 11 .…”
Section: Epidemiologymentioning
confidence: 64%
“…Comparisons of the factor structure across gender demonstrated that the differences were due largely to 1 item: cry. The implications of this work in the context of studies with other populations are discussed.Depression is among the most frequently acknowledged psychopathologies in American Indian communities, second only to suicide and alcoholism (Shore & Manson, 1983). Its occurrence has been linked to a variety of circumstances, including frequent interpersonal conflict (Ross & Davis, 1986), prolonged, unresolved grief (Jilek-All, Jilek, & Flynn, 1978), chronic familial instability (Resnik & Dizmang, 1971), unemployment (Travis, 1984, and rapid culture change (Kraus & Huffier, 1979).…”
mentioning
confidence: 99%
“…Indian youth, especially during adolescence (Berlin, 1986;Blum, Harmon, Harris, Bergeisen, & Resnick, 1992;Shore & Manson, 1983). In two studies of high school students, a greater proportion of American Indian adolescents met diagnostic criteria for clinical depression than did non-Native adolescents (cited in U.S. Congress, Office of Technology Assessment, 1990).…”
Section: Introductionmentioning
confidence: 99%